Does Experience Moderate The Effect Of Fintech Payment Convenience, Hedonic Motivation, Financial Literacy On Financial Management Behavior Of Msmes In Demak Regency ? - Wulandari, Erni; Ira Setiawati; Prianka Ratri Nastiti (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the influence of fintech payment convenience, hedonic motivation, and financial literacy on financial management behavior with experience as moderation variables in MSMEs in Demak Regency. The population of this study is MSME actors totaling 100 respondents, using quantitative research methods. The determination of the number of samples was carried out by statistical calculation using the slovin formula with an error rate of 10%. This study uses a purposive sampling technique. This study uses the Partial Least Square (PLS) method with the SmartPLS 3 operating system. The data used is primary data obtained through the distribution of questionnaires offline using paper and online using google forms to respondents. The results of this study show that the ease of fintech payments has a negative and insignificant effect on financial management behavior. Hedonic motivation has a positive and significant effect on financial management behavior. Financial literacy has a positive and significant effect on financial management behavior. Experience is not able to strengthen the relationship between the ease of fintech payments, hedonic motivation, financial literacy and financial management behavior. Keywords: Ease of fintech payment, Hedonic motivation, Financial literacy, Experience, Financial management behavior, MSME.